Colon Cancer-Related Genes Identification and Function Study Based on Single-Cell Multi-Omics Integration - Sun, Xuepu; Guo, Yu; Zhang, Yu; Zhao, Peng; Wang, Zhaoqing; Wei, Zheng; Qiao, Haiquan (Frontiers in Cell and Developmental Biology, 2021)
Transcriptome and DNA methylation of colon cancer at sing cell level are used to identify marker genes and improve the diagnosis as well as therapies. Seven colon cancer subtypes are recognized based on the single cell RNA sequence and the differentially expressed genes regulated by dysregulated methylation are identified as marker genes for different types of colon cancer. Comparing with normal colon cells, marker genes of different types show very obvious specificity, especially the genes of up-regulated genes in tumor. Functional enrichment analysis for marker genes indicate possible relation between colon cancer and nervous system disease, moreover, the weak immune system is verified in colon cancer. Markers expression up as well as methylation down in colon cancer promote tumor development in extensive mechanism so that there is no biological process be enriched in different types.